Comparative study of short- and long-term outcomes of laparoscopic-assisted versus open rectal cancer resection during and after the learning curve period. Issue 19 (May 2017) - Wu, Yunhua; Sun, Xuejun; Qi, Jie; Wei, Guangbing; Cui, Feibo; Gao, Qi; Yu, Junhui; Wang, Kai; Zheng, Jianbao
Abstract : Abstract: Laparoscopic-assisted rectal resection (LAR) has been widely used to treat rectal cancer. However, it has a steep learning curve. In this study, we aimed to investigate the effects of the learning curve on the outcomes of LAR. All consecutive patients with rectal cancer undergoing LAR or open resection (OR) between 2010 and 2015 were included in this retrospective analysis. The learning curve was determined, and patients were divided into 2 phases: the learning curve and the expert period. The short-term perioperative data in the 2 phases and the long-term survival in the learning phase were compared between the LAR and OR groups. A total of 491 patients were included in this study. Inflection of the learning curve based on the operation time of LAR was at the 40th case. A total of 233 patients underwent surgery (112 LAR and 121 OR) during the learning period. In this period, LAR had a longer operation time, less blood loss, and a higher total cost (all P  < .05). The 3-year overall survival rates between the LAR and OR groups were similar (69.74% vs 75%; P  = .32). A total of 258 patients underwent surgery (169 LAR and 89 OR) during the expert period. Significant differences in total cost, estimated blood loss, postoperative hospital stay, and recovery of bladder and bowel functions were identified in this period (all P  < .05). LAR during the learning period has fewer benefits in terms of postoperative recovery than OR. However, the long-term outcomes are equivalent.